2000
DOI: 10.1046/j.1365-2265.2000.00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroidectomy for primary hyperparathyroidism induces positive uncoupling and increases bone mineral density in cancellous bones

Abstract: In primary hyperparathyroidism patients, the major increase in bone mineral density following parathyroidectomy occurs within 3 months. Parathyroidectomy resulted in a marked increase in bone mineral density of cancellous bones compared to that of cortical bones. The early increase in bone mineral density was due to a preferential activation of bone formation over bone resorption as evidenced by changes in bone metabolic markers. Our results also showed that the preoperative levels of bone metabolic markers ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…These differences remained significant even after adjusting for AD-SoS values and other confounding factors such as age and BMI. Therefore, it is very probable that the different QUS pattern between PHPT and OP patients is caused mainly by the different microarchitectural bone characteristics described in the several studies on the two diseases [6][7][8][9]29]. Clear evidence exists that QUS parameters are related not only to bone density but also to structural bone characteristics [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences remained significant even after adjusting for AD-SoS values and other confounding factors such as age and BMI. Therefore, it is very probable that the different QUS pattern between PHPT and OP patients is caused mainly by the different microarchitectural bone characteristics described in the several studies on the two diseases [6][7][8][9]29]. Clear evidence exists that QUS parameters are related not only to bone density but also to structural bone characteristics [19].…”
Section: Discussionmentioning
confidence: 99%
“…Namely, while in OP patients the connectivity of bone tissue is lost because of trabecular perforation [5], in PHPT patients bone loss is due to an increase in cortical porosity and a reduction in cortical width [6,7]. After parathyroidectomy, cortical porosity decreases and cortical width increases, whereas trabecular bone structure does not change [8], although BMD increases because of positive uncoupling between bone formation and bone resorption [9]. PHPT patients with reduced BMD show an increased risk of bone fracture in comparison with the general population [10], although such an increase seems to be less than that which is found in osteoporotics.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that pHPT patients rapidly and persistently regained BMD predominantly at trabecular sites but gained little increase in BMD at cortical sites after PTX over the short-term (Abe et al ., 2000). Many studies have demonstrated that pHPT patients rapidly and persistently regained BMD predominantly at trabecular sites but gained little increase in BMD at cortical sites after PTX over the short-term (Abe et al ., 2000).…”
mentioning
confidence: 99%
“…The PHPT is a relatively common endocrine disorder, which is usually presented by incidental detection of hypercalcemia (1, 3). Although osteitis fibrosa is the characteristic presenting abnormality, in recent years, this skeletal disorder has become rare as the first presenting feature.…”
Section: Discussionmentioning
confidence: 99%
“…Although osteitis fibrosa is the characteristic presenting abnormality, in recent years, this skeletal disorder has become rare as the first presenting feature. However, osteopenia is still a common and important feature of PHP, and histopathologic studies and measurements of BMD have demonstrated stimulated bone resorption and a high-turnover bone loss, which is more dominant in cortical bones than in cancellous bones (3). …”
Section: Discussionmentioning
confidence: 99%